COVID-19 and public private partnerships in Asia and the Pacific guidance note. (COVID-19 in Asia and the Pacific guidance notes.)
COVID-19 is significantly affecting the development and life cycle stages of PPP projects in the region. This has led to disruptions in trade, production, and supply chains as well as sharp declines in consumption and investment.The guidance note looks at these impacts as well as the implications for contractual arrangements. It also presents governance practices that will help mitigate the risks and outlines important considerations for governments in regard to managing PPP projects for a post-pandemic recovery.